Glaciovolcanic edifices. Correlation of passage zone with ice sheet slope at Bláfjall tuya, NE-Iceland - Anna Margrét Sigurbergsdóttir 1989- (2023)
Bláfjall tuya in northern Iceland was formed in a volcanic eruption within a Pleistocene ice sheet. It is located well north of the old ice divide, where ice flow was predominantly from south to north. The elongated structure of the tuya is oriented parallel to the flow of the ancient glacier. Bláfjall is one of the tallest glaciovolcanic edifices in the area, standing 1222 meters a.s.l., highest on the southern end and capped with effusive lava flows. Whilst the elevation of the mountain decreases to the north, the thickness of the lava cap is greatest in the northern part and generally decreases to the south. Its thickness generally ranges from a few meters to few tens of meters, with a maximum of about 200 m. The water level of the englacial lake or lakes, which either partially or completely surrounded the tuya during its formation, would have to become progressively lower towards the north for the deposition of effusive lava layers. The northern part is predominantly formed by an advancing lava delta which suggests the ice sheet was thinning towards the south, with either continuous meltwater drainage or repeated drainage in the form of jökulhlaups. Apparently, both the thickness of the ice sheet and the direction of ice flow direction exerted major control on the height and elongation of the Bláfjall tuya. Bláfjall er móbergsstapi á öræfunum sunnan Mývatns. Það myndaðist í eldgosi undir ísbreiðu seinustu ísaldar, norðan ísaskila. Ísflæði jökulsins var því að mestu frá suðri til norðurs á meðan gosinu stóð. Ílöng lögun fjallsins liggur samhliða straumstefnu ísflæðisins á myndunartímanum. Bláfjall rís 1222 metra yfir sjávarmáli, hefur þykka hraunahettu og er eitt af hæstu móbergsmyndunum svæðisins. Hraunahettan er að meðaltali nokkrir tugir metrar á þykkt en mælist allt að 200 metrar þar sem hún er þykkust. Fjallið er hæst syðst, nærri gígnum, og lækkar til norðurs. Hraunahettan er hins vegar þynnst syðst og þykknar eftir því sem norðar dregur. Fjallið virðist hafa vaxið í norðurátt, í skriðstefnu ...